2016
DOI: 10.15420/ecr.2016:29:2
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography For the Detection of the Vulnerable Plaque

Abstract: Post-mortem OCT studies have defined the optical appearance and morphological characterisation of the plaque, 9-14 showing an overall good agreement with histology and high reproducibility (see Table 1). OCT can identify normal wall segments and early atherosclerotic lesions, 15,16 and also perform tissue characterisation in advanced atherosclerotic lesions (see Table 2). 5 The major plaque types identified by OCT are fibrous plaques, appearing as a signal-rich, homogeneous region with low signal attenuation; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 92 publications
0
13
0
Order By: Relevance
“…During onset of thrombembolic events in arteresclerosis, vulnerable plaques play an important role [10]. Histological studies of coronary atherosclerosis suggest that plaques can be identi ied by thin ibrous caps that overlie large, often necrotic lipid cores [11,12]. A multimodal assessment of plaque vulnerability involving the combination of systemic markers, new imaging methods, for example, ultrasonic investigation, ct-imaging and MRI that target in lammatory and thrombotic components, and the potential of emerging therapies may lead to a new strati ication system for atherothrombotic risk and to a better prevention of atherothrombotic stroke [3][4][5][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…During onset of thrombembolic events in arteresclerosis, vulnerable plaques play an important role [10]. Histological studies of coronary atherosclerosis suggest that plaques can be identi ied by thin ibrous caps that overlie large, often necrotic lipid cores [11,12]. A multimodal assessment of plaque vulnerability involving the combination of systemic markers, new imaging methods, for example, ultrasonic investigation, ct-imaging and MRI that target in lammatory and thrombotic components, and the potential of emerging therapies may lead to a new strati ication system for atherothrombotic risk and to a better prevention of atherothrombotic stroke [3][4][5][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, development of artificial intelligence could in the future predict changes in plaque vulnerability [16,176]. In a feasibility study by Guo et al, the authors demonstrated that machine learning methods could be used to accurately predict changes in plaque vulnerability using morphological and biomechanical factors from multi-modality imagebased 3D fluid-structure interaction coronary model [176].…”
Section: Will There Be a Biomarker For Unstable Plaque In The Future?mentioning
confidence: 99%
“…However, in the recent years, advancements in intravascular ultrasound (IVUS), high-resolution magnetic resonance imaging (MRI) studies positron emission tomography-computed tomography (PET-CT), and modern angiographic modalities with implemented optical coherent tomography (OCT) brought an in vivo insight into vulnerable plaques [8][9][10][11][12][13][14][15]. Intravascular OCT, a high-resolution (10-20 µm) light-based intravascular imaging technique, although bearing some noteworthy limitations, is currently the most relevant intracoronary imaging method as it can distinct vulnerable from stable plaque in a fairly reliable manner [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the significance of the work by Kobayashi et al [1] lies in the OCT-induced elucidation that very high sUA levels are associated with plaque rupture and the formation of red thrombi, which are often observed in culprit lesions in ACS patients. Although syndromic manifestations in ACS arise from a single focal lesion, multiple unstable lesions are not uncommonly observed clinical observations in atherothrombosis [13, 14]. Also, nonculprit lesions of patients with myocardial infarction demonstrate a complicated morphology in coronary angiography and are associated with more events during follow-up [14-16].…”
mentioning
confidence: 99%
“…Although syndromic manifestations in ACS arise from a single focal lesion, multiple unstable lesions are not uncommonly observed clinical observations in atherothrombosis [13, 14]. Also, nonculprit lesions of patients with myocardial infarction demonstrate a complicated morphology in coronary angiography and are associated with more events during follow-up [14-16]. One study investigated the association between sUA levels and plaque instability in nonculprit lesions in ACS patients using OCT and found that thin-cap fibroatheromas and cholesterol crystals were more frequent in the high UA tertile group, which further elucidated the relationship between UA and unstable plaques as a predictor of a poor prognosis in ACS patients [17].…”
mentioning
confidence: 99%